Querying data with Transact-SQL exam 70-761 certification training : prepare to take the Microsoft 70-761 exam and work towards your MCSA SQL 2016 database development certification - Long, Mark (O'Reilly, 2017)
"Microsoft's SQL Server database platform is dominant in the enterprise database marketplace, making those with MS SQL Server skills highly sought after in any job market. Possessing a Microsoft Certified Solutions Associate (MCSA) SQL 2016 Database Development certificate tells employers worldwide that you have these skills. Earning the certificate requires you to pass two exams: The MS 70-761 and the MS 70-762. This course prepares you to pass MS 70-761. MS 70-761 is all about Transact-SQL, the programming language central to working with MS SQL Server. Designed for those relatively new to the world of MS SQL Server, the course covers the basics of database development and then moves into an easy-to-understand, step-by-step, detailed presentation of how to work with Transact-SQL. This course features lots of hands-on coding with plenty of animations, photos, and screenshots all designed to help you grasp Transact-SQL's underlying concepts and technologies."--Resource description page.